Harnessing Technology for Marketing Success: A Case Study in the Culinary Tourism Sector - Abdi, Abdi; Rohmah, Irva Yulia (PT Mattawang Mediatama Solution, 2024)
This study investigates effective marketing strategies for Bukit Amaish Cafe & Resto in Pare-Pare, utilizing insights from relevant literature and qualitative data gathered from seven informants, including the owner, manager, marketing staff, and customers. The findings reveal that leveraging data analytics and social media significantly enhances consumer engagement and brand awareness. However, the limitations include a focus on a single location, which may not fully represent broader trends in the culinary tourism industry. The implications of this research emphasize the importance of data-driven approaches in developing targeted marketing strategies. It is recommended that Bukit Amaish invest in staff training for upselling techniques and optimize social media engagement. Additionally, expanding research to include diverse locations could provide further insights into effective marketing strategies within the culinary sector.